A Systematic Review Of Key Bacterial Pathogens And Therapeutic Strategies In Gastrointestinal Infections - Isramilda; Oktaviani, Fifin (Journal of health research and technology, 2025)
Gastrointestinal (GI) infections pose a significant global health challenge, particularly in resource-limited settings, due to their high morbidity and mortality. This systematic review explores the epidemiology, pathogenesis, clinical manifestations, diagnostics, and therapeutic strategies associated with major bacterial pathogens, including Salmonella, Campylobacter, Shigella, pathogenic Escherichia coli, Clostridioides difficile, Helicobacter pylori, and Vibrio species. Emphasis is placed on the growing issue of antimicrobial resistance and the potential of innovative therapies such as probiotics, bacteriophages, and microbiome-based interventions. The review synthesizes evidence from 274 selected studies published between 2015 and 2025, following PRISMA guidelines. By integrating traditional and molecular diagnostic approaches and evaluating emerging treatments, this study aims to support evidence-based strategies for effectively managing and preventing bacterial GI infections across diverse populations.